New Coronavirus Infection (COVID-19) and Digestive System - V. T. Ivashkin; A. A. Sheptulin; O. Yu. Zolnikova; A. V. Okhlobystin; E. A. Poluektova; A. S. Trukhmanov; E. N. Shirokova; M. I. Gonik; N. I. Trofimivskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The study reviews current evidence on digestive system lesions provoked by the new COVID-19 coronavirus infection.Key points. Alongside the destructive impact on respiratory system, COVID-19 manifests itself in gastrointestinal symptoms (nausea, vomiting, diarrhoea) that may precede respiratory signs and prevail in the clinical picture of infection. Patients with chronic inflammatory bowel diseases receiving immunosuppressive therapy are at elevated risk of severe COVID-19 progression. The new coronavirus infection may induce liver damage with increased transaminase activity.Conclusion. Association of digestive system lesions with COVID-19 remains understudied and requires further research.